Moment-by-moment tracking of naturalistic learning and its underlying hippocampo-cortical interactions - Sebastian Michelmann (Nature Portfolio, 2021)
When listening to a story, humans learn about its structure and content. Here the authors reveal the neural processes behind episodic memory and predictive recall at a fine temporal scale in this naturalistic setting